2009
DOI: 10.1299/jfst.4.454
|View full text |Cite
|
Sign up to set email alerts
|

Extended Navier-Stokes Equations and Treatments of Micro-Channel Gas Flows

Abstract: Gas flows in micro-channels are, in general, theoretically treated with the Maxwell slip velocity as a boundary condition for the convection velocity at the wall. It is pointed out that wall slip is conventionally introduced in theoretical/numerical treatments of gas flows through micro-channels to obtain agreement with experimental results. In the present paper, we provide an alternative by solving the extended Navier-Stokes equations for compressible gas flows in micro-channels using the conventional no-slip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 22 publications
(46 reference statements)
0
18
0
Order By: Relevance
“…The extended Navier-Stokes equation (23) is also a possible and effective approach, and Dongari.et.al have reported that it can permit characteristic phenomena such as the Knudsen paradox in the transition regime (24) . Nevertheless, it is found that this macroscopic approach can give accurate and comparable solutions to kinetic-type approaches for flows within the slip regime.…”
Section: Couette/poiseuille Flow With Slip Velocity Boundarymentioning
confidence: 99%
“…The extended Navier-Stokes equation (23) is also a possible and effective approach, and Dongari.et.al have reported that it can permit characteristic phenomena such as the Knudsen paradox in the transition regime (24) . Nevertheless, it is found that this macroscopic approach can give accurate and comparable solutions to kinetic-type approaches for flows within the slip regime.…”
Section: Couette/poiseuille Flow With Slip Velocity Boundarymentioning
confidence: 99%
“…Predictions of flows using the conventional Navier-Stokes (NS) equations along with different velocity slip and temperature jump conditions at the wall (Arkilic et al, 1997;Karniadakis and Beskok, 2002;Colin, 2005;Karniadakis et al, 2005;Barber and Emerson, 2006;Dongari et al, 2007;Tang et al, 2007a,b;Weng and Chen, 2008;Cao et al, 2009;Chen and Bogy, 2010;Colin, 2012;Zhang et al, 2012b), 2. Modelling of flows employing higher order equations than the conventional NS equations (Hadjiconstantinou, 2000;Jin and Slemrod, 2001;Struchtrup and Torrilhon, 2003;Hadjiconstantinou, 2006;Shan et al, 2006;Ansumali et al, 2007;Lilley and Sader, 2008;Struchtrup and Torrilhon, 2008;Weng and Chen, 2008;Dongari et al, 2009;Roohi and Darbandi, 2009;Dongari et al, 2010), 3. Use of i) kinetic theory of gases (Loyalka, 1971;Cercignani, 1990), ii) Molecular Dynamic (MD) simulations (Bird, 1994;Zhang et al, 2012a), iii) Discrete Simulations Monte Carlo (DSMC) methods (Pan et al, 1999;Hadjiconstantinou, 2000), iv) Non-linear and linearised Boltzmann Equation (BE) (Cercignani, 1975(Cercignani, , 1988Li and Kwok, 2003) and v) Lattice Boltzmann Method (LBM) (Cornubert et al, 1991;Sbragaglia and Succi, 2005;Zheng et al, 2006;…”
Section: Introduction and Aim Of Workmentioning
confidence: 99%
“…Some of these works [6][7][8] were based on the idea of introducing the concept of the "volume velocity", which differs from the usual mass velocity by a small flux term derived from Fick's law. Others [16,18] introduced similar additional terms to model the self-diffusion of mass. Among those listed above, the works [15,29,38] appear to employ the closest conceptual approach to what we suggest here, namely, in [15,29,38] an ad hoc diffusion term was introduced directly into the Boltzmann equation (1.1) via the assumption of an additional empirical stochasticity of the molecular motion to complement the already present intermolecule collisions.…”
Section: Introductionmentioning
confidence: 99%